2020
DOI: 10.1016/j.ijfatigue.2020.105792
|View full text |Cite
|
Sign up to set email alerts
|

How does surface integrity of nanostructured surfaces induced by severe plastic deformation influence fatigue behaviors of Al alloys with enhanced precipitation?

Abstract: Effects on fatigue behaviors and microstructures of Surface Mechanical Attrition Treatment (SMAT) before or after precipitation aging have been investigated on two hardenable Al alloys. The aluminum alloy with high notch sensitivity (7075) should not be processed by SMAT as the generated low surface integrity is always detrimental to fatigue performances. On less notch sensitive alloys (2024), SMAT before aging formed smaller and denser precipitates, resulting in a high hardened depth, and microstructures more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…These negative behaviours were again attributed to the easier initiation of the fatigue cracks which was cancelling the improved crack propagation resistance due to the compressive residual stress layer [57,58]. Maurel et al studied the effect of SMAT duration when combined with ageing heat treatment on the fatigue behavior of two aluminium alloys, namely a 2024 and 7075 series [26]. Some samples were aged before SMAT and some after SMAT.…”
Section: Effect Of the Surface Integrity On Fatigue Crack Initiationmentioning
confidence: 99%
See 1 more Smart Citation
“…These negative behaviours were again attributed to the easier initiation of the fatigue cracks which was cancelling the improved crack propagation resistance due to the compressive residual stress layer [57,58]. Maurel et al studied the effect of SMAT duration when combined with ageing heat treatment on the fatigue behavior of two aluminium alloys, namely a 2024 and 7075 series [26]. Some samples were aged before SMAT and some after SMAT.…”
Section: Effect Of the Surface Integrity On Fatigue Crack Initiationmentioning
confidence: 99%
“…SMAT or similar treatments were suggested to be efficient ways to enhance the fatigue behavior of many metallic alloys due to the coupled effect of microstructure, hardening gradient, and compressive residual stresses [17][18][19][20][21][22]. However, some manuscripts suggested that SMAT can be detrimental for some materials or if the chosen set of parameters for the SMAT treatment is not optimized [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Rough surface is a negative factor, as it generally causes local stress concentration that promotes crack nucleation from the surface, thereby degrading the fatigue performance of materials [56][57][58]. According to Maurel et al [3], the high notch sensitivity of AA7075 alloy could explain why SMAT cannot improve its high cycle fatigue resistance, compared to other aluminum alloys such as AA2024. Moreover, according to Akiniwa et al [28], the fatigue strength of harder materials is very sensitive to defects.…”
Section: Effect Of Smat On Torsional Fatigue Propertiesmentioning
confidence: 99%
“…Therefore, extensive studies have been conducted to understand the fatigue behavior of high strength aluminum alloys over the past decades. Most of these studies were performed under uniaxial loading [2][3][4][5], but little data could be obtained for torsional fatigue. However, with the increase in structural design requirements and the improvement in testing systems, torsional fatigue behavior of structures is gaining increasing attention, but always constitutes a challenging research subject.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation